Pengaruh Penambahan Jenis Gula Terhadap Berat dan Tebal Nata de Soya - Baiq Dina Hardianti (LPPM Universitas Qamarul Huda Badaruddin, 2019)
This research uses an experimental research type with a quantitative approach. The purpose of this study was to determine whether there is an effect of adding the type of sugar to the weight and thickness of Nata de Soya. This research uses a Factorial Complete Randomized Design (RALF) which consists of two factors, namely the type of sugar and the use of varying sugar weights. The results showed that the treatment that got the highest yield was a2b2 = 640 grams with an average thickness of 4.1 cm. the lowest weight and thickness is a2b4 treatment = 186 grams with a thickness of 0.5 cm. the results of the study were analyzed using the F test, resulting (0,000) <significance level (0.05), so that H0 was accepted and H1 was rejected. This means that there is no effect of adding the type of sugar to the weight and thickness of Nata de Soya.